Family Values and the Image of Mother in Druten's I Remember Mama (Journal of the College of Basic Education, 2022)
In many of his plays, the playwright John Van Druten depicts the life of everyday people in everyday situations. Druten is one of the successful American playwrights in 1940s. Actually, Druten was an English playwright and theatre director. He began his career in London, and later moved to America becoming an American citizen. Among his famous plays Old Acquaintance (1940), The Voice of the Turtle (1943), I Remember Mama (1944), The Mermaid Singing (1946) and his Critics' Circle Award winning play I Am a Camera (1951). The present paper studies the importance of family values in Druten's play I Remember Mama through the image of mother in this play. The paper starts, in the first section, with a brief introduction to realism in modern American drama; it moves gradually to seek the family values in Druten's I Remember Mama in the second section. Some family values are very clear in the play specifically the sacrifice and selflessness. Other values are mingled within more technical side of things, and some others are associated with the structure and integrity of the play itself. Druten used these values as the main elements to depict the image of the mother of the Hanson's family. The paper is rounded up with a conclusion in section three, which states briefly the main findings of the study.